2019
DOI: 10.3390/cancers11040487
|View full text |Cite
|
Sign up to set email alerts
|

CYFRA 21-1 in Lymph Node Fine Needle Aspiration Washout Improves Diagnostic Accuracy for Metastatic Lymph Nodes of Differentiated Thyroid Cancer

Abstract: Fine needle aspiration cytology (FNAC) and washout thyroglobulin (Tg) measurements are the standard for evaluating a metastatic lymph node (LN) in thyroid cancer. However, patients rarely benefit from these procedures due to false results. This study aims to identify a reliable biomarker that significantly improves the diagnosis of metastatic LNs, in addition to FNAC and washout Tg. This study analyzed 130 LNs that were suspected to have metastases on thyroid ultrasonography, from June 2016 to December 2017. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
3
18
0
Order By: Relevance
“…Thyroid carcinoma is the most common malignant endocrine tumor with an incidence that has remarkably increased in the past 10 years [1][2][3][4][5]. Thyroid carcinoma ranks ninth in cancer incidence worldwide and accounts for 5.1% of the total estimated cancer burden in females in 2018 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid carcinoma is the most common malignant endocrine tumor with an incidence that has remarkably increased in the past 10 years [1][2][3][4][5]. Thyroid carcinoma ranks ninth in cancer incidence worldwide and accounts for 5.1% of the total estimated cancer burden in females in 2018 [6].…”
Section: Introductionmentioning
confidence: 99%
“…65 CYFRA21-1 is a fragment of CK19, whose washout fluid shows great potential in diagnose the metastatic lymph nodes of DTC when combined with FNA. 66 Though its concentration in serum presents good value in diagnosing head and neck cancer, including oral, oropharyngeal, hypopharyngeal, and laryngeal cancers, 67 it do not perform well in discerning benign and malignant thyroid nodules. Early to 2008 and 2010, someone has claimed that its level has no manifested difference between benign and malignant thyroid nodules.…”
Section: Tumor-related Markersmentioning
confidence: 99%
“…As tumor metastasis is a serial dynamic process involving the separation of tumor cells from the originating site, many tumor cells are destroyed during the metastatic cascade, releasing the structural component CK19 into the circulation [12]. Similarly, a previous study showed that serum Cyfra 21.1 levels obtained from fine-needle aspiration washout were significantly increased in metastatic lymph node in thyroid cancer [24]. We postulate that at the time of metastasis, the cleavage of CK19 by caspase 3 resulted in increased synthesis and elevation in serum levels of Cyfra 21.1.…”
Section: Discussionmentioning
confidence: 91%